Development of a methodology to determine the gap in medical professionals in outpatient care based on the epidemiological profile of demand - Palomino-Carrasco, Cecilia Nelly (2025)
Objective: To develop and validate a methodology for determining the gap in medical professionals in outpatient care within the Rebagliati Healthcare Network of EsSalud, based on the epidemiological profile of demand. Materials and methods: A mixed-methods study was conducted analyzing 1.96 million outpatient visits between July 2022 and June 2023. Diagnoses were categorized into five age groups, selecting the 80% most frequent. A modified Delphi technique was applied with family physicians, pediatricians, internists, and geriatricians to determine the most appropriate specialty for each frequent diagnosis. Subsequently, 2.04 million outpatient visits from 2023 were processed to assign the corresponding specialty of care and estimate demand by medical specialty. The required physician-hours and number of professionals per specialty were calculated and compared with estimates derived from the traditional methodology based on historical service production. Results: Most outpatient visits corresponded to low-complexity conditions, underscoring the need to strengthen the presence of primary care physicians. A significant shortage of general practitioners and family physicians was identified, along with an oversupply of specialists at the primary care level. Compared with the traditional approach, the proposed methodology allocated 1.5 times more first-level physicians and fewer clinical and surgical specialists. Conclusion: The methodology based on the epidemiological profile of demand provides a more accurate estimation of the medical workforce gap, aligning more closely with the population’s healthcare needs. It may contribute to optimizing the distribution of specialists by reallocating them from low-complexity consultations to areas requiring higher levels of specialization.